Supporting Preprimary Parent Engagement in South Sudan : Lessons from Eight Parent Education Programs - World Bank (World Bank, Washington, DC, 2020)
This literature review aims to understand the design and content of successful preprimary parenting programs specifically those implemented in fragile, conflict, and violent contexts. This document serves as a resource guide for the creation of a preprimary parenting program for the South Sudanese context, to enhance school readiness of children between the ages of 3 to 5 years through basic literacy, numeracy, and socio emotional skills. This paper provides a brief overview of the benefits of parent engagement early in life and explores eight parenting programs whose design and implementation can be useful to increase the engagement of parents in preprimary skill development in South Sudan. Bearing in mind the context of South Sudan, five key criteria that guided selection of the programs included: (i) low cost of implementation, (ii) use of local resources, (iii) creation of contextually relevant curriculum, (iv) supporting parents who do not know how to read and write, and (v) evidence of benefits following empirical testing. It is important to have a clear picture of the lived experience of young children, their families and communities in South Sudan prior to designing a program that is relevant and appropriately meets their needs. This paper provides a brief overview of existing literature on the benefits of parent engagement early in life and explores eight parenting programs that have been designed and implemented in Ghana, Chad, Cameroon, Rwanda, Liberia, Syria, Jordan, and Lebanon to boost parent engagement in the lives of their young children. By doing this, the paper aims to create a resource document that can inform the development of a context-specific parenting program model for South Sudan.